Proceedings of the 7th ACM &Amp; IEEE International Conference on Embedded Software - EMSOFT '07 2007
DOI: 10.1145/1289927.1289963
|View full text |Cite
|
Sign up to set email alerts
|

E-FRP with priorities

Abstract: E-FRP is declarative language for programming resourcebounded, event-driven systems. The original high-level semantics of E-FRP requires that each event handler execute atomically. This requirement facilitates reasoning about E-FRP programs, and therefore it is a desirable feature of the language. But the original compilation strategy requires that each handler complete execution before another event can occur. This implementation choice treats all events equally, in that it forces the upper bound on the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Unlike FRP, our approach is agnostic about time, thus not lending itself to reasoning about temporal properties. Soft real-time guarantees have been studied for at least some FRP variants [23]. It may be possible to give a semantics for RVs in terms of FRP.…”
Section: Comparison To Functional Guis and Frpmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike FRP, our approach is agnostic about time, thus not lending itself to reasoning about temporal properties. Soft real-time guarantees have been studied for at least some FRP variants [23]. It may be possible to give a semantics for RVs in terms of FRP.…”
Section: Comparison To Functional Guis and Frpmentioning
confidence: 99%
“…Nevertheless, RVs can beneficially be used together with lenses and we view them as complementary. Recent developments in monadic lenses applied to User Interfaces 23 and lenses with notifications [8] could help simplify our formalisation to its true core objective: a data-binding language between typed reactive elements.…”
Section: Comparison To Functional Guis and Frpmentioning
confidence: 99%
“…To address this limitation, resource-bounded variants of FRP were studied ( [8], [13], [14]). Recently, it was shown that a variant called priority-based FRP (P-FRP) [8] combines both the semantic properties for FRP, guarantees resource boundedness, and supports assigning different priorities to different events.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that a variant called priority-based FRP (P-FRP) [8] combines both the semantic properties for FRP, guarantees resource boundedness, and supports assigning different priorities to different events. In P-FRP, higher priority events can preempt lower-priority ones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation